Fortalecimiento de la gestión empresarial en las pequeñas y medianas empresas en Ecuador, a partir del uso de herramientas cualitativas y cuantitativas - Pérez Guerra, Yailí (2016)
Globalization has placed organizations under a difficult situation, pushing and evolving models and standards of enterprise management. This reality is no exception to small and medium enterprises (SMEs) which must reach a coherent and adequate management, independent of the organization size. SMEs in Ecuador have a strongimportance for the national economy because of the number of job positions they offer and because of their financial contribution.It is known that a determinant element in the enterprise results are decision processes which can become stronger if supported using qualitative and quantitative tools which minimize risks and uncertainty levels and permits execution to be fast and efficient; resulting in better outcomes for organizations. In front of this need the objective of the following work is to analyze a group of quantitative and qualitative tools that support the process of decision making and that contribute to the enterprise development on SMEs. As result of this research a panoramic view of Ecuador’s enterprise sector is offered and some tools and techniques are recommended that could be used with projections to obtain better economic results.